Efeito de diferentes intensidades de perturbação na estrutura da comunidade de peixes de riachos - Nassin, Fabiano Carneiro (Universidade Federal de São Carlos, 2009)
Land use changes can impact aquatic communities, compromising water quality due to the physical and chemical degradation of the habitat. This study evaluated the hypothesis that stream fish communities differ relative to disturbance degree, determined by a habitat degradation gradient. Thus, the objectives of this project were: to survey streams not yet studied in central São Paulo State, located in a predominantly agricultural landscape; describe fish communities in streams subject to different degrees of habitat degradation and relate the fish communities to environmental variables. The study was conducted in low-order streams in the lower river Jacaré-Guaçu watershed, located in the Water Management Unit Tietê-Jacaré (UGRH-13). Twelve streams with different degrees of disturbance were assessed using a protocol for rapid assessment (PAR). In each 100m-reach, we estimated the PAR, and measured stream width and depth, physical and chemical variables of the water, and substrate diversity. Streams were classified in quality categories as preserved, altered and impacted, and fish communities were sampled with an electrofishing equipment. Most streams sampled were impacted or altered, with negative scores due to stream margin use, vegetation characteristics, sedimentation, water flow characteristics, velocity/depth regimes, temperature, pH, total dissolved solids and electrical conductivity. Fish communities presented low values of species richness and diversity, represented by a total of 20 species. Characiformes contributed with 40% of collected species, followed by Siluriformes (30%), and Perciformes, Gymnotiformes and Cyprinodontiformes (10% each). Representative species included Phalloceros caudimaculatus (41% of total abundance), Astyanax altiparanae (22%) and Poecilia reticulata (9%), whereas each of the other species contributed less than 5% of total abundance. Highest species diversity was found in streams classified as impacted, but there was a large variation, and relationship with PAR was found.. There is positive relationship of species richness with the increases in stream width, depth and electrical conductivity; evenness increased with stream width and pH, whereas diversity was positively related increases in stream depth and pH. Fish faunal composition did not differ among streams in different degradation classes identified by PAR, and were more influenced by stream physical characteristics and the presence of local impact factors, such as small barriers. Thus, although the habitat of most streams show evidence of degradation, fish communities did not reflect directly this result.
Keywords: Ecologia de comunidades; Impacto ambiental; Peixe; Ictiofauna; CIENCIAS BIOLOGICAS::ECOLOGIA